Collaborative Autoethnography Qualitative Study on Essential Tips for Successful Graduate Dissertation Writing: Insights from Academicians in Higher Education - Nemes, Joyce; Nuñez, Jayrome (International Journal of Qualitative Research, 2025)
The graduate dissertation is a crucial milestone in academic studies, serving as a definitive demonstration of a student's research maturity. However, recent research reveals that many graduate students face significant challenges during the writing process. Drawing from the personal experiences of two supervisors from Tanzania and the Philippines, each with years of experience in higher education, this study provides essential, experience-driven tips to help post-graduate students navigate this complex endeavor. The study synthesizes systematic observations of recurring challenges, misconceptions, and struggles that students encounter across diverse academic disciplines. It offers practical guidance on key aspects, including familiarization with institutional guidelines, strategic topic selection, effective proposal writing, coherent data presentation, analysis, discussion of findings, and proper citation and referencing. By following the tips outlined in this study, post-graduate students can enhance their chances of producing high-quality work that meets institutional standards and showcases their academic abilities, ultimately improving their success during the dissertation writing process. This research addresses a critical gap in existing literature and suggests that future studies should explore the applicability of these strategies in various institutional contexts.